Comprehensively utilization of spent bleaching clay for producing high quality bio-fuel via fast pyrolysis process. (1st January 2020) - Xu, Lujiang; Chen, Shijia; Song, He; Liu, Yang; Shi, Chenchen; Lu, Qiang
Abstract: High-quality bio-fuel (low oxygen content and acid value, high calorific value) was produced by catalytic pyrolysis of clay oil over calcined clay. Both feedstock (clay oil) and catalyst (calcined clay) were obtained from spent bleaching clay (SBC) deriving out of edible oil plants. The calcined clay was characterized with inductively coupled plasma-atomic emission spectrometry (ICP-AES), N2 adsorption/desorption analyses, X-Ray Diffraction (XRD), temperature programmed desorption of ammonia and carbon dioxide (NH3 -TPD and CO2 -TPD). Catalytic pyrolysis experiments were conducted to investigate the effects of several parameters on the product distribution, including pyrolysis temperature, weight hourly space velocity (WHSV) and residence time. The optimal conditions for produce high quality bio-fuel were 550 °C with WHSV of 2.5 h −1 and residence time of 1.65 s. The low heating value of bio-oil was increased by 13%–46.36 kJ/g, as long as the acid value was decreased by 97% to 1.16 mg/g KOH. The calcined clay catalyst showed slight deactivation after 4 cycles. Therefore, fast pyrolysis process is a rapid and efficient method of valorising spent bleaching clay from waste oils for high quality bio-fuel. Highlights: Spent bleaching clay was Comprehensively used to produce high quality bio-fuel. The calcined clay was served as catalyst and showed good deoxidation efficiency. Catalyst characterizations & pyrolysis parameters were investigated systematically. The calcined clay catalyst showed slight deactivation after 4 cycles. The LHV of bio-oil increased by 13% and the acid value decreased by 97%.